Acute Bowel Obturation: Treatment Outcomes - A. L. Charyshkin; E. A. Keshyan (Креативная хирургия и онкология, 2021)
Background. Two-stage colostomy is a common choice in treatment for obstruction-complicated colorectal cancer.Aim. Research into paracolostomy complications in obese and non-obese patients.Materials and methods. Material on obstruction-complicated colorectal cancer was collected from 50 patients divided into two cohorts by the body mass index (BMI). Cohort 1 contained 25 patients with BMI <24, and cohort 2 — patients with BMI >30.Results. Compared to cohort 1 with BMI <24, obese cohort 2 revealed more paracolostomy complications, the increase in parastomal skin lesions by 32% (p < 0.05), pyoinflammatory complications by 36% (p < 0.05) and abscesses by 24% (p < 0.05).Discussion. Paracolostomy complications in patients with BMI >30 are due to obesity, a poorly fitting colostomy bag, faecal leakage, skin irritation, infection and crude coagulation in haemostasis. Stoma gradually becomes difficult to visualise, faecal leakage continues and the paracolostomy space is poorly drained in obese patients, contributing to pyoinflammatory parastomal complications.Conclusion. The main causes of pyoinflammatory parastomal complications in obese patients are a low stoma positioning and poor paracolostomy drainage. The circumstances described warrant improvement of colostomy techniques in obese patients.